Post treatment thyroid dysfunction and obesity in children with acute lymphoblastic leukemia and non-Hodgkin’s lymphoma: a brief report - Ali Ghasemi (Tehran University Medical Journal, 2014)
Background: In most children with Acute Lymphoblastic Leukemia (ALL) and Non Hodgkin’s Lymphoma (NHL) who have received chemotherapy with and without radi-otherapy, some late effects due to treatment may occur such as endocrinopathies. Methods: We evaluated growth criteria (including short stature, obesity) and thyroid test function in 50 children with ALL (n= 25) and NHL (n= 25) 3-17 year-old in remis-sion period who randomly received chemotherapy with (n= 25) or without (n= 25) radi-ation such as our treatment groups. The values for height, weight and BMI in less than 5th or more than 95 th percentile considers abnormal. Results: Six (12%) patients were in less than 5th percentile height (short stature). Two patients (4.0%) had over-weight and 48 (96%) were in normal range of BMI. Six (12%) patients were in less than 5th and 3 (6%) were in more than 95 th weight percentile. There was no significant difference between two different treatment groups for TSH (P= 0.662 (but there was a significant difference between these groups in case of T4 (P= 0.049(. Mean and SD for T4 in patients with chemotherapy alone was less than in whom received chemotherapy plus radiotherapy. There was no significant difference between ALL and NHL groups for TSH, T4 (P= 0.567, 0.528 respectively). Two boys with ALL without history of radiation had hypothyroidism that had based on their la-boratory data. Conclusion: Regarding to effects of thyroid dysfunction on short stature and obesity in adolescent with ALL and NHL, we suggest to have more attention about growth, thy-roid test to avoid late side effect of malignancy treatment.